(untitled) (KYAMC Journal, 2025)
We report the case of a young man of 28 years, who was hospitalized with the complaints of headache for 5 days and weakness in both upper and lower limbs for 10 days. He has the history of Ependymal excision at 4th ventricle in the past. The young man was found to have recurrence of Ependymoma with infiltration to the spinal cord after doing MRI of brain and spinal cord. Ependymoma is a rare type of brain tumor. It arises from Ependymal cells which line the spinal cord and ventricles of the brain. Ependymomas can develop in both children and adults. Ependymal tumors represent approximately 1.6% of all primary central nervous system tumors. Occurrence of Ependymal tumor in both brain and spinal cord is very rare, this review emphasizes that recurrence of Ependymoma after surgery can occur affecting both brain and spinal cord. KYAMC Journal Vol. 16, No. 01, April 2025: 48-50